Mycobiota associated with Platypus cylindrus (Coleoptera: Curculionidae, Platypodidae) in cork oak stands of North West Algeria, Africa - Belhoucine, Latifa; Bouhraoua, Rachid T; Meijer, Martin; Houbraken, Jos; Harrak, M Jamal; Samson, Robert A; Equihua-Martinez, Armando; PUJADE-VILLAR, JULI (AFRICAN JOURNAL OF MICROBIOLOGY RESEARCH, 2011)
Platypus cylindrus (Coleoptera: Curculionidae, Platypodidae) is an important insect pest of the cork oak. These beetles maintain symbiotic relationships with many fungi that serve especially as food for the adults and larvae but also intervene in the mechanisms of establishment of the insect by further weakening the host-tree. 270 samples were taken by 3 sources: Galleries (30), mycangia and intestinal contents of male and female insects and intestinal contents of mature larvae (60 each). The results show the presence of 42 species of ambrosia fungi among which 17 are new to this association. The mycetophagy of these beetles is very rich and consisted essentially of Ophiostomatales. Other groups of fungi playing different roles were also isolated: entomopathogenic, antagonistic, saprophytic but especially pathogenic for the tree host. This group consists of many species and their dissemination by the insect and the inoculation in trees may have fatal consequences by accelerating the cycle of declining affected trees. In the present paper, we discuss the fungal species associated to the beetle, identified on the basis of phenotypic characters and ribosomal DNA sequences analysis, and their relationship with P. cylindrus.
Keywords: Ambrosia fungi; Forest of M'sila (Oran-Algeria); Platypus cylindrus; Quercus suber